Bit-wise parallel algorithms for efficient software correlation applied to a GPS software receiver. - Ledvina, B.M (IEEE Transactions on wireless communications)
A set of efficient algorithms for processing code-division multiple-access spread spectrum signals has been developed. They make use of bit-wise parallelism to process 32 samples simultaneously. These algorithms have been implemented in a real-time global positioning system software receiver. The receiver consists of a radio-frequency front end, a system of shift registers, a digital data acquisition card, and software that runs on a 1.73-GHz PC. The PC performs base-band mixing and pseudorandom noise code correlations in a manner that directly simulates a hardware digital correlator.